(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
One of the most common hypovitaminosis in pregnant women is a deficiency of iron and folic acid, leading to anemia - a condition in which the amount of hemoglobin (the oxygen carrier in red blood cells) is reduced. Tissues damaged during childbirth heal very slowly. Severe postpartum depression, osteoporosis, caries develops, the condition of the skin and hair changes. An effective method of replenishing vitamin and mineral deficiency during pregnancy and lactation is regular intake of the Emfetal vitamin and mineral complex, containing 12 vitamins and 10 minerals. Its action is due to the effects of its constituent vitamins and minerals. Vitamins participate in metabolism as catalysts and regulators of biochemical and physiological processes. Minerals are vital elements for metabolic processes in the human body, participate in the construction of cells and tissues of the body, and in the activity of enzyme systems. Emfetal contains 3 fat-soluble (A, E and D) and 9 water-soluble vitamins (B1, B2, B5, B6, B9, B12, C, PP, H).